Consecuencias de la lectoescritura en el aprendizaje de los estudiantes de los terceros años de Educación Básica de la Unidad Educativa “Narciso Cerda Maldonado” durante el año lectivo 2016 – 2017” - Naranjo Riera, Miguel Ángel (2018)
The main purpose of this research is to carry out a literacy innovation design, throughout methodology strategies to enhance the communicative abilities of third graders “at Unidad Educativa Narciso Cerda Maldonado.” This research has great relevance since it provides valuable knowledge about reading, writing, and also suggests some didactic proposals in order to help teachers to encourage, stimulate, and strengthen the reading and writing teaching-learning process. Moreover, the literacy has been associated with a series of skills to make it up as a competence, which it is defined as a superior process to be accomplished for all members of our society who use reading and writing with a practical purpose and delimitated it as a cultural component.